ANALISIS PROGRAM KURIKULUM, KINERJA GURU TERHADAP PEMBENTUKAN KARAKTER SISWA DENGAN KEPEMIMPINAN KEPALA SEKOLAH SEBAGAI VARIABEL MODERATING - Saraswati, Indriani Saraswati; Adji, Askardija R. Adji; Susanti, Riana Susanti; amir, Ja'far Amir (Indo-Fintech Intellectuals: Journal of Economics and Business, 2025)
Character formation has become a primary educational program in Indonesia. A quantitative study employing the SEM-PLS approach was conducted to investigate the relational patterns among principal leadership, curriculum programs, teacher performance, and student character formation. Online questionnaires were distributed to 85 respondents, comprising teachers and students, and subsequently analyzed using SmartPLS4 software. This research explores the influence of curriculum programs, teacher performance, and principal leadership on student character formation. The findings indicate that curriculum programs and teacher performance significantly contribute to student character development, while principal leadership acts as a moderator, influencing the effectiveness of these two factors. This study suggests the necessity of a holistic approach in character education to achieve optimal learning outcomes.